Direct Vision, Transfascial (DVT) Approach to Submuscular Reservoir Placement in Patients Undergoing Multicomponent Penile Implant Surgery Following Prior Pelvic Surgery or Radiation Therapy. Issue 2 (27th December 2021) - Kava, Bruce R.; Levine, Amanda; Hauser, Nicholas; Masterson, Thomas; Ramasamy, Ranjith
ABSTRACT: Background: Submuscular reservoir placement has fulfilled a critical need for patients desiring multicomponent penile implants following pelvic surgery and radiation therapy. Passage of the reservoir through the inguinal canal into the submuscular space is often challenging and carries the risk of the reservoir being placed unknowingly outside of the targeted space. Aim: To evaluate the safety and accuracy of a direct vision, transfascial (DVT) approach to submuscular reservoir placement. Methods: We retrospectively reviewed outcomes for consecutive patients undergoing DVT submuscular reservoir placement abstracted from a large IRB-approved database at our institution. Postimplant cross-sectional imaging performed on many of these patients was used to ascertain the final location of the reservoir. Outcomes: Outcome measures included the perioperative and intermediate-term safety and complications of the procedure. Postimplant imaging ascertained the accuracy in providing patients with a submuscular reservoir. Results: There were 107 DVT submuscular reservoirs placed in 100 consecutive patients. No intraoperative complications occurred, there were no postoperative rectus hematomas, and there were 4 (3.7%) postoperative infections. With a mean follow up of 17.5 +/- 20.5 months there was one reservoir herniation, one patient had autoinflation, and one patient required repositioning of a high riding pump. There were 4 mechanical malfunctions requiring revision at a median of 74 months (range: 69–108 months.) following implant placement. Of the 43 patients who underwent imaging: 34 (79%) reservoirs were accurately positioned, 5 (12%) were in the lateral abdominal wall, 1(2%) was in the retroperitoneum, and 3 (7%) were intraperitoneal. Intraperitoneal reservoirs occurred exclusively in postcystectomy patients. Clinical Implications: The DVT approach is technically safe, although a slightly higher than expected infection risk was noted. It provides accurate reservoir placement for the majority of imaged patients. Postcystectomy patients have a risk of insidious intraperitoneal reservoir placement. Preoperative counseling should mention this and postimplant imaging may be considered for some of these patients. Imaging may also helpful prior to future revision surgery in order to identify and remove insidious intraperitoneal reservoirs. Strengths and Limitations: We investigated 100 patients, almost half underwent cross sectional imaging. Weaknesses include the retrospective nature of this single-institutional study, which may not have similar outcomes at other centers. Conclusion: DVT submuscular reservoir placement is safe following pelvic surgery and radiation therapy. Despite careful and deliberate surgical technique imaging found that approximately 20% of reservoirs are not in their expected location. Intraperitoneal reservoirs are of concern, particularly in postcystectomy patients.